Glenoid wear and migration pattern of a humeral head resurfacing implant: a prospective study using radio stereometric analysis - Michael Axenhus, MD, PhD; Magnus Ödquist, MD, PhD; Hassan Abbaszadegan, MD, PhD; Olof Sköldenberg, MD, PhD; Björn Salomonsson, MD, PhD (JSES International, 2024)
Background: The humeral head resurfacing arthroplasty (HHR) is normally used as a hemi shoulder arthroplasty and has been in use for the treatment of Gleno-Humeral osteoarthritis (OA) of the shoulder for more than 30 years. Some studies, however, shows that anatomical total shoulder arthroplasty provides better improvement in function than a HHR for patients with OA. Reasons for this may be a progressive glenoid wear (GW) or loosening of the HHR. We, therefore, wanted to investigate the migration pattern of the HHR and also GW by using radio stereometric analysis (RSA). Methods: 21 patients (21 shoulders) with OA and a mean age of 64 years were enrolled in the study. They all received the Copeland humeral resurfacing head and were followed for 2 years with RSA. We evaluated the clinical outcome at 2 years with Western Ontario Osteoarthritis of the Shoulder (WOOS), EuroQol 5 dimension 3L and Constant Shoulder Score. In addition, we assessed data on WOOS and revisions until 5 years follow-up by using the local clinic data within the Swedish Shoulder Arthroplasty Register. Results: After an initial migration at two months the implants were stable in relation to the humerus with no statistically significant difference between the 2 months and the 2 years value (P = .23). The GW continued to increase during the study period with an initial migration of mean 2.3 mm and at 2 years 3.5 mm with a statistically difference between the 6 months and 2 years value (P = .046). The WOOS, EuroQol 5 dimension 3L and Constant Shoulder Score were all improved at 2 years compared to the preoperative values. We found a weak correlation between GW at 2 years and the WOOS score at 2 and 5 years, but these did not reach statistical significance. There were 4 revisions within 5 years after the primary operation, all due to pain. Conclusion: The marker-free RSA can be used in clinical studies for assessing migration in HHR implants and was also for the first time used to measure GW. The Copeland HHR seems to obtain a secure fixation in the humerus but shows continuous GW up to two years.